Experimental Studies and Numerical Simulation Stress Analysis of Mortar Base Plate Under Impact Loading - Piotr Bieniek; Mirosław Tupaj; Krzysztof Szwajka (Shock and Vibration)
The subject of the work was the analysis of the stress state of the base plate and the comparison of the obtained strain measurement values with the results of FEM numerical analyses. During the field shooting tests, the load on the base plate was in the form of a dynamic force applied in its center. Firing under field conditions was carried out with ballistic mortar shells from the ground at an angle of elevation of the mortar barrel ensuring maximum range of 45°. In order to obtain input data for the FEM analysis, the strains occurring on the base plate were measured using strain gauge rosettes. Based on the measured strains, the reduced maximum stresses were calculated. Simulation studies described so far in the literature have ignored the aspect of variable soil elasticity and, consequently, the different stiffness of the support areas of the base plate. This work is a new approach to the issue of variable stiffness of individual support areas, which is not uniform under the entire surface of the plate. A new methodology for conducting numerical tests was proposed, which consisted in identifying individual stiffnesses of selected areas of the plate model in order to obtain stress values close to the real ones recorded during shooting tests. The convergence of the results of reduced stresses calculated from measurements of actual deformations occurring on the mortar base plate during firing and numerical simulations of the computational model ranged from 70.4% to 97.3%. The obtained test results prove the validity of the proposed approach to considering the stresses occurring in individual areas of the base plate, depending on the variable stiffness of the soil.